2014
DOI: 10.1021/la503142q
|View full text |Cite
|
Sign up to set email alerts
|

About the Role of Surfactants on the Magnetic Control over Liquid Interfaces

Abstract: The behavior of magnetically responsive aqueous Fe(III) surfactant solutions at liquid interfaces is analyzed. Such surfactants attracted much attention, because of the ability to manipulate interfaces by magnetic fields without any use of magnetic nanoparticles. A detailed analysis of the surface properties proves that the mixing of paramagnetic electrolyte solution with anionic, cationic and nonionic surfactants yields the similar magnetic response and no effect of the surfactant charge can be observed. We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 9 publications
7
26
0
Order By: Relevance
“…Even though intense research effort has been put on studying the magnetic effect on the properties and behaviour of water or other liquids, [18][19][20][21] only a few studies on their surface tension were reported. [22][23][24][25] This is true especially for relatively low magnetic elds, 26,27 as the one that can be produced with small permanent magnets used inside microuidic chips ($100 mT).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Even though intense research effort has been put on studying the magnetic effect on the properties and behaviour of water or other liquids, [18][19][20][21] only a few studies on their surface tension were reported. [22][23][24][25] This is true especially for relatively low magnetic elds, 26,27 as the one that can be produced with small permanent magnets used inside microuidic chips ($100 mT).…”
mentioning
confidence: 99%
“…With such an approach, only an apparent surface tension can be detected by the instrument. 27,30 In order to suppress the bulk component, which arises in the presence of a magnetic gradient, we constructed an experimental setup where surface tension measurements were performed using the pendant drop method inside highly uniform magnetic elds. Unlike ferrouid drops that can elongate along eld lines due to their strong magnetic response, 31 most common liquid drops maintain their shape under uniform elds.…”
mentioning
confidence: 99%
“…Degen et al recently used X-ray reflectivity (XRR) to provide insights into Fe accumulation at the interface for a 1-dodecyltrimethylammonium trichloromonobromoferrate (DTAF) [27]. They reported an extremely small layer thickness, as is typical of conventional surfactants, and suggested that this was not enough for paramagnetic response to occur from just surface iron ions.…”
Section: Magnetic Ionic Liquid Surfactants -Classmentioning
confidence: 99%
“…[8] In 2014, Degen et al investigated organic surfactants with paramagnetic FeCl 4 À as acounterion and concluded that there is no special "magnetic surfactant effect". [9] This last study motivated us to invest effort in preparing compounds in which the transition-metal species is an integral part of the head group. [10] One can expect that am agnetic torque will act directly on the surfactant molecule under appropriate conditions.W ei ntended to explore this effect in our current study.…”
mentioning
confidence: 99%